BOOK REVIEW: AI IN FOREIGN LANGUAGE LEARNING AND TEACHING: THEORY AND PRACTICE BY MARCEL DANESI - Hidayat, Ahmad Fadhel Syakir; Bahruddin, Uril; Mustofa, Syaiful; Abidin, Nadiah (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2025)
In AI in Foreign Language Learning and Teaching: Theory and Practice, Marcel Danesi underscores the ramifications of Artificial Intelligence (AI), including the use of tools like ChatGPT, on Foreign Language Teaching (FLT) and its critical components: language acquisition and teaching. Danesi covers several aspects of FLT to speak, write and assess, voicing their greatest concerns on the impact of AI. Danesi provides a balanced view, considering both the advantages and challenges of dependence on AI in language education. He articulates important ethical arguments on the impact of AI in education, particularly its failure to address students’ emotional and contextual concerns, while highlighting the gap human instructors fill. In addition, the book provides synthesis of the frameworks on the use AI technologies and pedagogical tools to improve FLT while maintaining the human dimension of teaching.